2020
DOI: 10.1029/2019ms001916
|View full text |Cite
|
Sign up to set email alerts
|

The Community Earth System Model Version 2 (CESM2)

Abstract: An overview of the Community Earth System Model Version 2 (CESM2) is provided, including a discussion of the challenges encountered during its development and how they were addressed. In addition, an evaluation of a pair of CESM2 long preindustrial control and historical ensemble simulations is presented. These simulations were performed using the nominal 1° horizontal resolution configuration of the coupled model with both the “low‐top” (40 km, with limited chemistry) and “high‐top” (130 km, with comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,063
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 1,405 publications
(1,080 citation statements)
references
References 155 publications
15
1,063
0
2
Order By: Relevance
“…During DJF, LENS exhibited too much divergence over the western Indian ocean (Figure 10c), which is a common feature among CMIP6 models ( Figure A1k) and was associated with too much precipitation in that region. In CESM2, the excess divergence is reduced and shifted further west and accompanies a reduction in the excess precipitation bias (Danabasoglu et al, 2019). Overall, the errors in the 200-hPa velocity potential field have been reduced in DJF, making CESM2 one of the top ranking models in this metric (Figure 10g).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 95%
See 1 more Smart Citation
“…During DJF, LENS exhibited too much divergence over the western Indian ocean (Figure 10c), which is a common feature among CMIP6 models ( Figure A1k) and was associated with too much precipitation in that region. In CESM2, the excess divergence is reduced and shifted further west and accompanies a reduction in the excess precipitation bias (Danabasoglu et al, 2019). Overall, the errors in the 200-hPa velocity potential field have been reduced in DJF, making CESM2 one of the top ranking models in this metric (Figure 10g).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 95%
“…These simulations are run under historical forcings (Hoesly et al, 2018;van Marle et al, 2017) until 2014. The coupled simulations are each initialized from different years from a preindustrial (i.e., perpetual year 1850 forcing) control that has been spun-up for over 1,000 years (Danabasoglu et al, 2019), while the prescribed SST simulations begin in 1950. For each ensemble we will only consider the period from 1979 to 2014 for comparison with modern reanalyses over the satellite era.…”
Section: Cesm2mentioning
confidence: 99%
“…Most CMIP6 models also projected a significant weakening of the AMOC (Weijer et al 2020). Here we focus on the role of the AMOC in the transient response of the climate system to changes in greenhouse gas forcing, a topic that has not been fully addressed, using two CMIP6 models: the Community Earth System Model version 2 (CESM2; Danabasoglu et al 2019) and the Energy Exascale Earth System Model version 1 (E3SM1; Golaz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The model experiments described here were performed with the WACCM6. Details on CESM2 and WACCM6 model configurations, including an overview of the performance and new features, are described by Danabasoglu et al (2019) and Gettelman et al (2019), respectively. The WACCM6 atmospheric model uses a horizontal resolution of 1.25 o in longitude and 0.95 o in latitude, and 70 vertical layers, reaching up to 140 km height above sea level (6x10 −6 hPa).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The earlier version of the model shows a slowing of the AMOC for the RCP8.5 scenario similar to the WACCM6 CMIP6 SSP5-85 simulation, which is however much smaller. Danabasoglu et al (2019) found that the maximum AMOC strength in 8 https://doi.org/10.5194/esd-2019-76 Preprint. Discussion started: 3 December 2019 c Author(s) 2019.…”
Section: Atlantic Meridional Overturning Circulation Changesmentioning
confidence: 99%